The impact of mental fitness exercises on decision-making among futsal players - علي, م.م مسار حمزة; دهام, م.م ميرند مطانس; Al-Jubouri, Prof. Dr. Haitham Mohammed (Sulaimani Journal for Humanities, 2026)
Our current era is characterized by rapid change and development in all aspects of life, especially in the field of sports, which has received considerable attention and care from most countries worldwide. Sports, particularly futsal, have witnessed rapid and effective development in recent years. Futsal is the most popular sport, requiring high levels of mental and technical skill, as well as decisive decision-making abilities, to elevate players' performance and develop their various skills. This development is a result of scientific studies and research conducted by experts to address the challenges and obstacles they face in a scientific and well-considered manner, aiming to achieve the best results and accomplishments at the local, continental, and global levels. The importance of this research lies in its focus on the impact of mental fitness on offensive decision-making in futsal players. It aims to modify training methods and performance styles to enhance decision-making, based on the belief that training, especially in mental aspects, yields positive results through continuous training, enabling players to reach their peak performance. By developing and applying mental fitness exercises to an experimental research sample to determine their effectiveness on dependent variables, the study concluded that there was a clear and tangible improvement in decision-making during offensive transitions among futsal players. The study recommended incorporating mental fitness exercises into training programs due to their significant effectiveness in developing mental abilities, particularly decision-making.
Keywords: Mental fitness; decisionmaking; futsal players